Liberty & equality in Caribbean Colombia, 1770-1835 - Helg, Aline, 1953- (University of North Carolina Press, 2004)
After Brazil and the United States, Colombia has the third-largest population of African-descended peoples in the Western hemisphere. Yet the country is commonly viewed as a nation of Andeans, whites, and mestizos. Aline Helg examines the historical roots of Colombia's treatment and neglect of its Afro-Caribbean identity.